Possible shunt compensation strategies based on conservative power theory - Marafão, Fernando P. [UNESP]; Brandão, Danilo I. [UNESP]; Paredes, Helmo K. Morales; Da Silva, Luiz C.P. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Considering the Conservative Power Theory (CPT), this paper proposes some novel compensation strategies for shunt passive or active devices. The CPT current decompositions result in several current terms, which are associated with specific physical phenomena (average power consumption P, energy storage Q, load and source distortion D, unbalances N). These current components were used in this work for the definition of different current compensators, which can be selective in terms of minimizing particular disturbing effects. Compensation strategies for single and three-phase four-wire circuits have also been considered. Simulation results have been demonstrated in order to validate the possibilities and performance of the proposed strategies. © 2010 IEEE.
Keywords: Active power filters; Compensation strategies; Harmonics; Hybrid filters; Reactive compensation; Selective compensation; Unbalance compensation; Active power Filter; Compensation strategy; Active filters; Electric wiring; Technical presentations